2018
DOI: 10.1002/1873-3468.13064
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of hydrogen gases and bile acids in the gut microbiome

Abstract: The human gut microbiome refers to a highly diverse microbial ecosystem, which has a symbiotic relationship with the host. Molecular hydrogen (H ) and carbon dioxide (CO ) are generated by fermentative metabolism in anaerobic ecosystems. H generation and oxidation coupled to CO reduction to methane or acetate help maintain the structure of the gut microbiome. Bile acids are synthesized by hepatocytes from cholesterol in the liver and are important regulators of host metabolism. In this Review, we discuss how g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 77 publications
0
72
1
Order By: Relevance
“…Moreover, lower abundances of Eisenbergiella , Oscillospira , Ruminococcaceae NK4A214 group and Synergistia in CS and all RS groups suggested that these four genera are unlikely to be involved in the degradation of complex carbohydrates. Both Bilophila and Eggerthella are involved in bile acid metabolism . Previous studies have indicated that bile acid promotes the expansion of Bilophila , while amylopectin rather than amylose increases the production of bile acid .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lower abundances of Eisenbergiella , Oscillospira , Ruminococcaceae NK4A214 group and Synergistia in CS and all RS groups suggested that these four genera are unlikely to be involved in the degradation of complex carbohydrates. Both Bilophila and Eggerthella are involved in bile acid metabolism . Previous studies have indicated that bile acid promotes the expansion of Bilophila , while amylopectin rather than amylose increases the production of bile acid .…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes generate a diverse metabolite repertoire that is proposed to mediate the effects of gut microbiome on host health and disease, some metabolites can promote metabolic benefits on body weight and glucose control, such as short-chain fatty acids like acetate, propionate and butyrate [12][13][14]. Importantly, molecular hydrogen(H 2 ), with a recent recognition of being a novel biologically-active gas exhibiting antioxidant, antiapoptotic, anti-inflammatory, cytoprotective and signaling properties and having great potential as a preventive and therapeutic medical gas [15][16][17], can be generated by fermentative metabolism in anaerobic ecosystems [18,19]. Molecular hydrogen has long been identified as a main component of intestinal gas in humans and respiratory hydrogen gas excretion can indicate intestinal hydrogen gas production [20].…”
mentioning
confidence: 99%
“…Hydroxysteroid dehydrogenases (HSDH) are responsible for the cleavage of two protons in the molecule (simple hydrogenation). In the human organism, the epimerization of the hydroxyl groups occurs via stereospecific oxidation followed by the stereospecific reduction of the oxo groups [ 35 ]. In the human gut, microorganisms of the genera Bacteroides, Clostridium, Escherichia, Eggerthella, Eubacterium, Peptostreptococcus, and Rumniococcus are primarily responsible for these reactions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%